Morphologic Differences Observed by Scanning Electron Microscopy According to the Reason for Pseudophakic IOL Explantation. Issue 5 (September 2015) - Fernández-Buenaga, Roberto; Alio, Jorge L.; Ramírez, José M.; Salazar, Juan José; Prause, Jan Ulrik; Ramírez, Ana I.; De Hoz, Rosa; Rojas, Blanca; Triviño, Alberto
Purpose: To compare variations in surface morphology, as studied by scanning electron microscopy (SEM), of explanted intraocular lenses (IOLs) concerning the cause leading to the explantation surgery. Methods: In this prospective multicenter study, explanted IOLs were analyzed by SEM and energy-dispersive X-ray spectroscopy. The IOLs were explanted in the centers of the research group from 2006 to 2012. The primary procedure was phacoemulsification in all cases. Results: The study evaluated 40 IOLs. The main causes for explantation were IOL dislocation, refractive error, and IOL opacification. Those explanted due to dislocation demonstrated calcifications in 8 lenses (50%), salt precipitates in 6 cases (37.5%), and erythrocytes and fibrosis/fibroblasts in 2 cases (12.5%). In the refractive error cases, the SEM showed proteins in 5 cases (45.5%) and salt precipitates in 4 lenses (36.4%). In IOL opacification, the findings were calcifications in 2 of the 3 lenses (66.6%) and proteins in 2 lenses (66.6%). Conclusions: A marked variation in surface changes was observed by SEM. Findings did not correlate with cause for explantation. Scanning electron microscopy is a useful tool that provides exclusive information regarding the IOL biotolerance and its interactions with surrounding tissues.